Radiofrequency Ablation on Autonomously Functioning Thyroid Nodules: A Critical Appraisal and Review of the Literature - Cesareo, Roberto; Palermo, Andrea; Pasqualini, Valerio; Manfrini, Silvia; Trimboli, Pierpaolo; Stacul, Fulvio; Fabris, Bruno; Bernardi, Stella (Frontiers in Endocrinology, 2020)
Background: Thyroid nodules are an extremely common occurrence, as their prevalence in the general population is estimated to range between 50% and 70%. Some of these nodules are autonomously functioning such that they can cause hyperthyroidism over time. In this case, surgery and radioiodine represent the standard of care. Nevertheless, patients might have contraindications or be unwilling to undergo these treatments. Minimally-invasive ultrasound-guided techniques, such as laser and radiofrequency ablation (RFA), have been recently introduced into clinical practice as an alternative treatment for symptomatic benign thyroid nodules. Due to their efficacy and tolerability, these techniques have become increasingly available and their usage has been extended also to autonomously functioning thyroid nodules (AFTN). Methods: in this narrative review, we will describe the studies reporting the therapeutic effects of RFA on AFTN, the studies reporting how RFA compares to the other treatment modalities, as well as the current indications for the use of RFA in patients with AFTN. For this purpose, a comprehensive literature search was independently conducted by three investigators on PubMed, EMBASE, and the Cochrane Library from inception up to February 2020 to identify published articles concerning the effects of RFA on AFTN. Results and conclusions: Current consensus statements and guidelines support the notion that RFA should be regarded as a first-line therapy for non-functioning benign thyroid nodules, while it remains a valid second-line option for AFTN treatment in case of contraindications or patient unwillingness to undergo surgery or radioiodine.